2021
DOI: 10.1093/g3journal/jkab361
|View full text |Cite
|
Sign up to set email alerts
|

Accuracies of genomic predictions for disease resistance of striped catfish to Edwardsiella ictaluri using artificial intelligence algorithms

Abstract: Assessments of genomic prediction accuracies using artificial intelligence (AI) algorithms (i.e.,, machine and deep learning methods) are currently not available or very limited in aquaculture species. The principal aim of this study was to examine the predictive performance of these new methods for disease resistance to Edwardsiella ictaluri in a population of striped catfish Pangasianodon hypophthalmus and to make comparisons with four common methods, i.e.,, pedigree-based best linear unbiased prediction (PB… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 76 publications
(95 reference statements)
1
3
1
Order By: Relevance
“…Inclusion of highly significant SNPs in genomic prediction models that included the c 2 did not have noticeable impacts on the prediction accuracy for tagging weight. This is likely due to the limited size of the significant SNPs obtained from genotyping by sequencing (GBS) platform but our observation here is consistent with previous findings for disease resistance traits in the same population of striped catfish P. hypophthalmus (Vu et al, 2021). In studies where the c 2 estimates were not included, Luo et al (2021) also found there were no advantages of preselected SNPs in genomic prediction models using ssGBLUP, WssGBLUP and BayesB for resistance to Edwardsiella tarda that causes acute symptoms with ascites in Japanese flounder (Paralichthys olivaceus).…”
Section: Can Ssgwas Alleviate the Impacts Of The C 2 Omission On The ...supporting
confidence: 92%
See 3 more Smart Citations
“…Inclusion of highly significant SNPs in genomic prediction models that included the c 2 did not have noticeable impacts on the prediction accuracy for tagging weight. This is likely due to the limited size of the significant SNPs obtained from genotyping by sequencing (GBS) platform but our observation here is consistent with previous findings for disease resistance traits in the same population of striped catfish P. hypophthalmus (Vu et al, 2021). In studies where the c 2 estimates were not included, Luo et al (2021) also found there were no advantages of preselected SNPs in genomic prediction models using ssGBLUP, WssGBLUP and BayesB for resistance to Edwardsiella tarda that causes acute symptoms with ascites in Japanese flounder (Paralichthys olivaceus).…”
Section: Can Ssgwas Alleviate the Impacts Of The C 2 Omission On The ...supporting
confidence: 92%
“…To date, studies in aquaculture species performed multi-trait genomic prediction are limited. Results from these studies showed that the accuracies of genomic predictions were not improved for fillet weight and fillet yield in Nile tilapia O. niloticus ( Joshi et al, 2020 ) or for survival status and survival time in striped catfish P. hypophthalmus ( Vu et al, 2021 ), likely because the high heritability of these two traits and their high genetic correlations; hence, adding one trait did not improve the prediction accuracy of the other. In yellowtail kingfish, Nguyen et al (2022) also showed that the benefits of multi- vs. univariate analysis depend on statistical methods used and genomic architecture of traits.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Here we compared two types of survival definitions; binary traits and continuous traits for our genetic evaluation, with both showing similar heritability estimates ( Table 3 ). While this result did not fit our earlier assumption that continuous traits would improve the results for heritability estimates via adding more survival time information to mortality events, similar findings have been reported for genetic analysis of survival data in experimental challenge tests on aquaculture species ( Joshi et al, 2021a ; Vu et al, 2022 ). Binary trait recording however, is much more simple (0, 1) to score than continuous survival data in practice and thus, should be considered more feasible for routine genetic evaluation in aquaculture breeding programs.…”
Section: Discussioncontrasting
confidence: 53%